Genetic diversity of Bartonella spp. in vampire bats and associated Streblidae bat flies in the Brazilian Amazon - Franco, Eliz Oliveira [UNESP]; de Oliveira, Laryssa Borges [UNESP]; Calchi, Ana Cláudia [UNESP]; de Mello, Victória Valente Califre [UNESP]; Lee, Daniel Antonio Braga [UNESP]; Arantes, Paulo Vitor Cadina [UNESP]; Graciolli, Gustavo; Machado, Rosangela Zacarias [UNESP]; Coelho, Taciana Fernandes Souza Barbosa; André, Marcos Rogério [UNESP] (Elsevier, 2025)
Among mammals, bats stand out as important reservoirs for Bartonella spp., second only to rodents. In Brazil, out of the 182 species of bats described, three are hematophagous: Desmodus rotundus, Diphylla ecaudata and Diaemus youngii. Considering that Bartonella species have been increasingly associated to disease in humans, the search for such agents in animal reservoirs and ectoparasites is crucial for understanding the epidemiology of bartonelloses. The present study aimed to investigate the occurrence and genetic diversity of Bartonella spp. in vampire bats and Streblidae bat flies in the Brazilian Amazon. For this purpose, 228 spleen samples of D. rotundus and 1 of D. youngi were collected from four states in the northern region of Brazil (Pará (n = 206/D. rotundus; n = 1/D. youngii), Roraima (n = 18/ D. rotundus), Amapá (n = 3/D. rotundus) and Amazonas (n = 1/D. rotundus). Additionally, 142 Streblidae bat flies were collected from 54 D. rotundus (23 Strebla wiedemanni and 118 Trichobius parasiticus) and one D. youngii (1 Trichobius diaemi). Seventy-three (31.9 %; 73/228) spleen samples of D. rotundus (62 from Pará, 9 from Roraima and 2 from Amapá) and 45/142 (31.7 %) Streblidae bat flies (1 T. diaemi, 8 S. wiedemanni and 36 T. parasiticus) were positive in qPCR for Bartonella spp. based on the nuoG gene. Phylogenetic analyses based on the gltA and rpoB genes positioned the sequences obtained together with genotypes previously detected in D. rotundus and bat-associated flies. High genotypic diversity was found among sequences obtained from bats and Streblidae flies (6 gtlA and 11 rpoB genotypes). The genotypes identified in D. rotundus in the present study were exclusively shared with sequences from Bartonella spp. detected in vampire bats, not overlapping with genotypes previously detected in non-hematophagous bats from Brazil. Most of the sequences detected in Streblidae bat flies formed unique genotypes for each dipteran species analyzed. The present study expanded the knowledge regarding the diversity of Bartonella genotypes in vampire bats and associated Streblidae flies.
Keywords: Amazon Forest; Bartonella; Bat flies; Chiroptera; Desmodus rotundus; Genotypic diversity